2018
DOI: 10.1103/physrevd.98.083015
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter distribution induced by a cosmic string wake in the nonlinear regime

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Gravity The universal gravitational effects of cosmic strings are probed via a variety of effects on the cosmic microwave background [401][402][403][404][405][406][407] and cosmological probes have produced limits [408][409][410][411][412][413][414][415] that are close to probing GUT-scale strings. There is a large body of work on searching for cosmic strings, but for now we just note they may also also be probed by gravitational wave searches [416][417][418][419][420][421][422][423][424] and large-scale structure [425][426][427], and even in 21 cm experiments [428], among other ideas. We refer to the recent review [168] for further discussion.…”
Section: E Rate Estimate and Signaturesmentioning
confidence: 99%
“…Gravity The universal gravitational effects of cosmic strings are probed via a variety of effects on the cosmic microwave background [401][402][403][404][405][406][407] and cosmological probes have produced limits [408][409][410][411][412][413][414][415] that are close to probing GUT-scale strings. There is a large body of work on searching for cosmic strings, but for now we just note they may also also be probed by gravitational wave searches [416][417][418][419][420][421][422][423][424] and large-scale structure [425][426][427], and even in 21 cm experiments [428], among other ideas. We refer to the recent review [168] for further discussion.…”
Section: E Rate Estimate and Signaturesmentioning
confidence: 99%
“…In a recent paper [11] (see also [12]) we began a study of the dark matter distribution induced by string wakes [13][14][15][16] inserted at z = 31, using a simulation box of lateral size L = 64M pc/h and np = 512 particles per dimension. We found that the string signals for a wake with a string tension of Gµ = 10 −7 can be identified down to a redshift of z ≥ 10.…”
Section: Jcap06(2020)016mentioning
confidence: 99%
“…A method used to extract the wake signal from the dark matter distribution was presented in [11] and can be summarized as follows: for any direction of the sphere, we consider an associated projection axis passing through the origin of the box. We then consider slices of the simulation box perpendicular to that axis at each point x of this axis with thickness given by the grid size of the simulation, and we compute the mass density δ(x) of dark matter particles in that slice as a function of x.…”
Section: Jcap06(2020)016mentioning
confidence: 99%
“…So the accuracy of their numerical CWTs can be verified by the corresponding analytical results. Finally, it should be noted that the CWT for 1D signals is not trivial in astrophysics and cosmology, as it is also applicable to a wide range of scenarios, such as analyzing the light curves of astronomical sources (e.g., Tarnopolski et al 2020;Ren et al 2022), subtracting the foreground emission from the 21 cm signal (e.g., Gu et al 2013;Li et al 2019), measuring the smallscale structure in the Lyman-α forest (e.g., Lidz et al 2010;Garzilli et al 2012;Wolfson et al 2021), investigating the time-frequency properties of the gravitational waves (e.g., Tary et al 2018), characterizing the 1D density fields (e.g., da Cunha et al 2018;Wang & He 2021;, and so on. We publicly release the Fortran 95 implementation of the fast CWT algorithms described in this manuscript 1 , in the hope that the community will use them to perform wavelet analysis of 1D signals.…”
Section: Introductionmentioning
confidence: 99%